Electroclinical findings and long‐term outcomes in epileptic patients with inv dup (15). (23rd January 2018) - Matricardi, S.; Darra, F.; Spalice, A.; Basti, C.; Fontana, E.; Dalla Bernardina, B.; Elia, M.; Giordano, L.; Accorsi, P.; Cusmai, R.; De Liso, P.; Romeo, A.; et al.
Abstract : Objective: To define the electroclinical phenotype and long‐term outcomes in a cohort of patients with inv dup (15) syndrome. Material and Methods: The electroclinical data of 45 patients (25 males) affected by inv dup (15) and seizures were retrospectively analysed, and long‐term follow‐up of epilepsy was evaluated. Results: Epilepsy onset was marked by generalized seizures in 53% of patients, epileptic spasms in 51%, focal seizures in 26%, atypical absences in 11% and epileptic falls in 9%. The epileptic syndromes defined were: generalized epilepsy (26.7%), focal epilepsy (22.3%), epileptic encephalopathy with epileptic spasms as the only seizure type (17.7%) and Lennox‐Gastaut syndrome (33.3%). Drug‐resistant epilepsy was detected in 55.5% of patients. There was a significant higher prevalence of seizure‐free patients in those with seizure onset after the age of 5 years and with focal epilepsy, with respect to those with earlier epilepsy onset because most of these later developed an epileptic encephalopathy (69.2% vs 34.4%; P = .03), usually Lennox‐Gastaut Syndrome in type. In fact, among patients with early‐onset epilepsy, those presenting with epileptic spasms as the only seizure type associated with classical hypsarrhythmia achieved seizure freedom ( P < .001) compared to patients with spasms and other seizure types associated with modified hypsarrhythmia. Conclusions: Epilepsy in inv dup (15) leads to a more severe burden of disease. Frequently, these patients show drug resistance, in particular when epilepsy onset is before the age of five and features epileptic encephalopathy.